If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 67 = 4y + 11 Reorder the terms: 67 = 11 + 4y Solving 67 = 11 + 4y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-4y' to each side of the equation. 67 + -4y = 11 + 4y + -4y Combine like terms: 4y + -4y = 0 67 + -4y = 11 + 0 67 + -4y = 11 Add '-67' to each side of the equation. 67 + -67 + -4y = 11 + -67 Combine like terms: 67 + -67 = 0 0 + -4y = 11 + -67 -4y = 11 + -67 Combine like terms: 11 + -67 = -56 -4y = -56 Divide each side by '-4'. y = 14 Simplifying y = 14
| 12+12x+12=90 | | (-8x^3)+72x=0 | | 12-8t= | | 0.005x^2+x+200=0 | | 3x+9+8x+11+5x+-8=180 | | 8x+10+8x=90 | | 12r^2+7rs-10s^2=12r^2-8rs+15rs-10s^2 | | (16y^3)-144y=0 | | 300=(6000/x) | | 24w^2(w-3)/3w^3(w-8) | | Ax-4y= | | -12k^2+7m-3+4k^2-3m= | | (13/20)/(1/4) | | 300=6000/x | | 12x+12x+12x=90 | | 12-15t= | | x+3(-3)=9 | | -53=-5x-2(-7x-14) | | 12+12+12=90 | | 18c^2-21c+24c-28= | | 2(x+2)+3x=2(x-1)+1 | | (6+3)(7-4i)= | | 2/3y-10=8 | | 2/5x-5=-9 | | 3.5(-2x-4)=10 | | 6+7(2x-3)=4-2(7x-3) | | x=2/(2/3) | | 12+12x=90 | | 3[x-4]+2x=6-x | | 4/3×y=12 | | 2=.75x-.625 | | -5+3x-2x=-9 |